Relationship between premolar extraction on the dimension of upper airway and tongue posture in skeletal class II malocclusion - Hartati Zuraidah Rangkuti; Aditya Rachmawati; Erliera Sufarnap (Majalah Kedokteran Gigi Indonesia, 2022)
Correction of skeletal Class II malocclusion with camouflage orthodontic treatment generally requires the extraction of the maxillary first premolars to provide space for retraction of the maxillary incisors. Retraction of incisors changes the position of the incisors and the dimensions of the dental arch, which can cause changes in tongue posture and affect the upper airway. The purpose of this study was to determine the relationship between premolar extraction on the dimensions of upper airway and tongue posture in skeletal Class II malocclusion. This study was designed as a retrospective cohort using lateral cephalometric radiographs before and after orthodontic treatment. The samples in this study consisted of 44 samples of adult patients (n = 44) aged 18-40 years, who were divided into 2 groups: 22 subjects treated without premolar extraction and 22 subjects treated with premolar extraction. Lateral cephalometric radiographic analysis were used to measure the dimensions of the upper airway by analyzing superior posterior airway space (SPAS), middle airway space (MAS), inferior airway space (IAS), vertical airway length (VAL), and tongue posture (tongue length and height tongue) using imageJ software. No Statistically significant different changes were observed as seen from the following results: SPAS (p = 0.709), MAS (p = 0.365), IAS (p = 0.562), (p = 0.401), tongue length (p = 0.578), tongue height (p = 0.086) in the sample group without extraction premolar. No significant alterations in the upper airway and tongue posture measurement were observed in the sample group with extraction premolar. Premolar extraction with retraction on upper incisors did not affect upper airway dimensions and toung posture in skeletal Class II malocclusion.